The Terms of Address Used by Local People in Sudaji Village North Bali - Andreyana, I Komang; Budasi, I Gede; Juniarta, Putu Adi Krisna (PEMA, 2025)
This study explores the use of terms of address by local speakers in Sudaji Village, Buleleng Regency. The research was motivated by a unique linguistic phenomenon in which Sudaji residents employ distinct address forms that differ from commonly used Balinese expressions. The study employed a descriptive qualitative design. Data were collected through observation, interviews, and audio recordings involving community members who fulfilled predetermined sociolinguistic criteria. All Balinese and Indonesian data were transcribed into English and analyzed using the Huberman qualitative model, including data collection, reduction, display, and conclusion drawing. The findings revealed five main categories of address terms: personal pronouns, kinship terms, first names, power and hierarchy-based terms, and mockery terms. Each category performs specific pragmatic functions such as signaling politeness, maintaining social hierarchies, constructing identity, indicating familiarity, or expressing intimacy. The analysis also showed that the selection of address terms is influenced by social variables including age, kinship, caste, familiarity, and situational context. The study concludes that Sudaji terms of address constitute an important cultural-linguistic resource that reflects local values and social structures, yet remain vulnerable to language shift as Indonesian becomes dominant in daily communication. Preserving these linguistic forms is therefore essential for maintaining local identity and enriching sociolinguistic studies in Bali.